Economic optimization of Co2 capture process using MEA-MDEA mixtures - Yong, R. (Trans Tech Publications Ltd, 2014)
Amine based solvents are extensively being used for post combustion carbon capture through absorption. Each solvent has its associated benefits and drawbacks. In order to overcome their drawbacks, a number of mixed amine streams have been used. However, this amalgamation step is usually overshadowed by process optimization issues and cost limitations. In this study, Monoethanolamine (MEA) â Methyldiethanolamine (MDEA) is used as the mixed amine-based solvent for removal of carbon dioxide. A simulation model of CO2 removal is developed using Aspen HYSIS to optimize the process. Subsequently, an economic analysis is constructed to evaluate the operating expenditure (OPEX) and capital expenditure (CAPEX) based on the simulation model, followed by sensitivity analysis. It is found that 25 wt MDEA and 15 wt MEA is the optimal operating condition that achieve the minimal total cost. Sensitivity analysis reveals that utilities cost affects the total cost significantly, followed by CAPEX. However, the effect of raw material costs on total cost is negligible. Â© 2014 Trans Tech Publications, Switzerland.